A survey and study on modern OS reliability and security - Muhammad Aqeel (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2021)
Current studies in operating systems focuses on either security or on reliability. However, current or modern OS platforms call for answers that match both styles of requirements. If we build not only best applications but also middleware and OS in a similar way, we can construct systems that not only are inherently stable however also can resist attacks from malicious programs and face up to errors. In this paper, we conduct an exploratory study on Modern OS reliability and security. We examine many real OS failure facts collected from distinct administrative and real time environments and present the results which show a number of the primary reasons of OS failures.